What should Niantic do to safeguard Poke?mon GO players? - Clinch, Nanette; Osland, Asbjr̜n (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Poke?mon GO has enjoyed a 35% boost in activity since May 2018, the highest user account since its debut in 2016. However, the increase in popularity has led to new problems for Niantic, an American software development company charged with responding to questions regarding the safety of Poke?mon GO. Excessive focus on the game has resulted in a number of injuries and deaths and Niantic must now decide how the company can protect itself both ethically and legally from class action lawsuits.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Niantic, Inc; Business enterprises -- Law and legislation -- United States; Class actions (Civil procedure) -- Prevention